Novel Quantification of Eggshell Surfaces in Dromaius novaehollandiae With Implications for the Fossil Eggshells of Oviraptorosauria (Dinosauria) - Joshua Hedge; Emerald Bender; Lindsay E. Zanno (Ecology and Evolution)
ABSTRACT The external surfaces of non‐avian dinosaur eggs are not usually smooth like those of their avian descendants. Unique ornamentation patterns sculpt the exterior of the eggs, a trait that is difficult to interpret because of its scarcity in modern taxa. One avian species that does homoplastically present similar external eggshell ornamentation to that of non‐avian dinosaurs is Dromaius novaehollandiae Latham, 1790, the emu. Here we use D. novaehollandiae eggs in conjunction with a clutch of oviraptorosaurian dinosaur eggs (NCSM 33576, Macroelongatoolithus carlylei) to test new methods of quantifying external eggshell ornamentation. Currently, the only scientific language for describing and comparing ornamentation styles in fossil ootaxa is restricted to qualitative categorization, which introduces issues of subjectivity and overly broad and overlapping typification. In this study, we derived and tested a new statistical quantitative approach to quantifying ornamentation that includes two existing functions of the molaR package in R previously applied to shape quantifications of fossil teeth, and ‘Orientation’, a novel function presented as a proxy for ‘direction’, needed to capture directionality. Results demonstrate that (1) the quantitative approach provides statistical backing to gross qualitative observations; (2) statistically significant differences exist between the ornamentation in D. novaehollandiae and M. carlylei, particularly in terms of relief; (3) intranest variation of M. carlylei can be demonstrated from harmonic mean p‐value differences between different pairs of eggs. This method offers a strong platform to consolidate quantitative measures with existing qualitative categories, improve the diagnoses of ootaxa and answer broad ecological and evolutionary questions regarding dinosaur reproduction. Moreover, wider application of the technique is encouraged for a multi‐proxy quantitative analysis of any paleontological surfaces, such as echinoderm tests, geological ripple marks or dentition.